2019
DOI: 10.3390/antiox8120614
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Ascorbic Acid, Deferoxamine and N-Acetylcysteine Improves Cardiac Fibroblast Viability and Cellular Function Associated with Tissue Repair Damaged by Simulated Ischemia/Reperfusion

Abstract: Acute myocardial infarction is one of the leading causes of death worldwide and thus, an extensively studied disease. Nonetheless, the effects of ischemia/reperfusion injury elicited by oxidative stress on cardiac fibroblast function associated with tissue repair are not completely understood. Ascorbic acid, deferoxamine, and N-acetylcysteine (A/D/N) are antioxidants with known cardioprotective effects, but the potential beneficial effects of combining these antioxidants in the tissue repair properties of card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…It is wellknown that LPS administration increases the expression of inflammatory cytokines (such as IL-1β, IL-6, and TNF-α) in the host through the TLR4/NFkB pathway but can also induce the PI3K/Akt pathway, which has been reported as an endogenous negative feedback regulator and/or compensatory mechanism of TLR4/NFkB-mediated proinflammatory responses, thus preventing an excessive innate immune response (25,26,33,34). In this sense, in our previous findings, we showed that I/R triggers the activation of p38 and JNK signaling pathways (11), which correspond to proapoptotic signals. In addition, a recent study showed that miR-20a has a protective action on cardiomyocytes subjected to sI/R by inactivating the p38 MAPK/JNK pathway and promoting cell viability (35).…”
Section: Lipopolysaccharide Activates Akt and Erk1/2 To Reduce Cardiamentioning
confidence: 54%
See 2 more Smart Citations
“…It is wellknown that LPS administration increases the expression of inflammatory cytokines (such as IL-1β, IL-6, and TNF-α) in the host through the TLR4/NFkB pathway but can also induce the PI3K/Akt pathway, which has been reported as an endogenous negative feedback regulator and/or compensatory mechanism of TLR4/NFkB-mediated proinflammatory responses, thus preventing an excessive innate immune response (25,26,33,34). In this sense, in our previous findings, we showed that I/R triggers the activation of p38 and JNK signaling pathways (11), which correspond to proapoptotic signals. In addition, a recent study showed that miR-20a has a protective action on cardiomyocytes subjected to sI/R by inactivating the p38 MAPK/JNK pathway and promoting cell viability (35).…”
Section: Lipopolysaccharide Activates Akt and Erk1/2 To Reduce Cardiamentioning
confidence: 54%
“…It is well-known that simulated ischemia/reperfusion (sI/R) can produce deleterious effects on CF viability; however, strategies to prevent sI/R injury have been poorly evaluated. This is an important topic since CFs participates in wound healing processes; therefore, viability protection is of utmost importance for their protection (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All concentrations of the active compounds were derived from previous published studies and DMD hiPSC-CMs were treated for 5 days prior to functional assay. Specifically: Quercetin, Naringenin, Kaempferol, and Hesperidin were used at 10 μM ( Gutiérrez-Venegas et al, 2014 ; Denaro et al, 2021 ); Diosgenin at 200 ng/mL ( Zhao et al, 2018 ); D -lactic acid at 10 μM ( Pohanka, 2020 ); Vitamin C at 10 μM ( Parra-Flores et al, 2019 ); Oxalic acid (10 μM) ( Liu et al, 2018 ); and Allicin at 10 μM ( Xiang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A huge generation of ROS at the beginning of reperfusion initiates lipid peroxidation and protein/nucleic acid oxidation, consequently activating pro-apoptotic pathways associated with p38-MAPK and JNK proteins [ 5 ]. In their manuscript, Parra-Flores et al [ 6 ] showed for the first time synergistic cytoprotective effect of ascorbic acid, deferoxamine, and N -acetylcysteine in simulated IR in CF. When added at low concentrations (10 μM) each at the onset of simulated reperfusion, the three antioxidants synergistically reduced intracellular ROS production and increased cell viability, induced phosphorylation of pro-survival kinases ERK1/2 (extracellular-signal-regulated kinases 1/2) and PKB (protein kinase B)/Akt, and decreased phosphorylation of the pro-apoptotic kinases p38-MAPK (proteins p38-mitogen-activated protein kinase) and JNK (c-Jun-N-terminal kinase).…”
mentioning
confidence: 99%